Impact of Emotional Intelligence, Percieved Stress and Academic self Efficacy On Happiness and Academic Performance - Singh, Amrinder (My University, 2019)
The study was done to see the impact of emotional intelligence and academic performance on academic self-efficacy, happiness and perceived stress. The sample consisted a total of 100 students of SAI institute, Patiala. Fifty students were boys and 50 students were girls. The age range was taken between 16-18 years. There were four questionnaires that were used for the study – The Schutte Self-Report Emotional Intelligence Test, Subjective Happiness Scale, Academicself-efficacy and Perceived Stress. For the result analysis, descriptive statistics to describe the results; correlation and regression was also used. Results showed that perceived stress had a negative relationship with happiness.
Keywords: Emotional Intelligence; Perceived Stress; Happiness; Academic Self-Efficacy; Academic Performance